Analisis Tingkat Kesadaran Penggunaan Free/Open Source Software (FOSS) pada Lembaga Pendidikan Indonesia - Arsa, Daniel; Nugraha, Hafiz (Prodi Sistem Informasi FST Universitas Jambi, 2020)
In this paper, the authors conducted small-scale research to determine the awareness, utilization, and barriers of school teachers, especially for Information and Communication Technology (ICT) teachers in using Free and Open Source Software (FOSS). In Indonesia, the utilization of applications and operating systems in educational institutions are still dependent on popular software, it makes the process of learning in schools often mentions the names or brands of certain software that are often used and are usually proprietary. In recent years, several parties have started the Free and Open Source Software (FOSS) movement to break the notion of using Proprietary software, FOSS is starting to be seen by users because of it’s affordability and freedom to use and contribute to developing software together. There are many FOSS that is often used such as Ubuntu, Mozilla Firefox, Moodle, OJS, and many more. The Indonesian government also encourages the use of FOSS in some institutions that have been introduced to FOSS. in this research, the author uses a quantitative approach with a descriptive survey method, it takes a sample from a population and uses a questionnaire as the main data aid. As a result, many obstacles were found that made teachers and students reluctant to use FOSS in their education, such as lack of knowledge, lack of training, availability of technology, and awareness of it.